If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4 = 8x + 15 Reorder the terms: 4 + 9x = 8x + 15 Reorder the terms: 4 + 9x = 15 + 8x Solving 4 + 9x = 15 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 4 + 9x + -8x = 15 + 8x + -8x Combine like terms: 9x + -8x = 1x 4 + 1x = 15 + 8x + -8x Combine like terms: 8x + -8x = 0 4 + 1x = 15 + 0 4 + 1x = 15 Add '-4' to each side of the equation. 4 + -4 + 1x = 15 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 15 + -4 1x = 15 + -4 Combine like terms: 15 + -4 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| Y=2x^2+24x+25 | | X^2+12x=-18 | | 12x-10y=14 | | 8S+4+2S-2= | | 2y-1y+15=22 | | 4(9-6x)=36 | | 4x^3+x^2+12x+3=0 | | 2=14k | | 49x^2+14xy+y^2=0 | | 4(3x+6)=-12 | | 6(-1x+2)=-60 | | 12+d=112 | | 5x(x+2)=80 | | 3x^5+12x^3= | | 2(1x+1)=14 | | 3x^5-12x^3= | | 4m-7=13 | | 243-(67+92)=84 | | 8x+30=7x+30 | | 36=2x+15 | | P=2x+3y | | -45*(-8)-(-13)= | | -8x-2+7x=-9 | | 13=2x+15 | | -2(2x+4)=-16 | | 2x-21-x+10=-1 | | 3(x+8)=45 | | 7(1+2x)=147 | | -6=11x-5x | | 5x+2(6)=3x(11) | | 15=5-2x | | 6(2x+7)=126 |